Pengaruh Relationship Quality terhadap Customer Value Co-Creation pada Sharing Economy Platforms (SEP) Generasi Z di Indonesia - Arofah, Rifka Utami; Winarni, Dwi; Hidayati, Farisa Nabila; Adlina, Rediarta Nisa (Universitas Batanghari, 2024)
This study aims to obtain the empirical evidence of relationship quality dimension variables that affecting value co-creation between companies (platform owners) and consumers, related to the exchange of goods and services, the exchange of knowledge, resource, and also experience. These things are useful to provide insights for business or platform owners to accelerate growth through a collaborative environment in order to improve the overall value proposition of all parties. This study took Generation Z respondents, namely the generation that born in 1996-2011 (Lanier, 2017). There are still few previous studies related to Sharing Economy Platforms (SEP) that focuses on a particular generation. The selection of Generation Z because they have a behavioral trend that prefers to spend their money to get life experiences such as traveling. Sampling technique is using Purposive Sampling with Smart PLS analysis tool. The results showed that trust and commitment affect value co-creation of users of SEPs in generation Z.